Update on the management of alcoholic steatohepatitis - Stickel, Felix; Seitz, Helmut K. (Journal of gastrointestinal and liver diseases, 2013)
mong heavy drinkers with liver disease, the development of severe alcoholic hepatitis (AH) is a serious complication. Prognosis is grave and associated with a high mortality due to liver failure, hepatorenal syndrome or intractable sepsis. Clinically, AH presents as a syndrome of progressive inflammatory liver injury in patients with recent or ongoing heavy alcohol consumption. Although approximately 20% of alcoholics undergoing liver biopsy reveal histological features of AH, only a minority progress to severe AH with markedly elevated serum liver enzymes, jaundice and impaired liver function. To establish the diagnosis of AH, histology is recommended but not mandatory. Prognostic scores include the Maddrey's discriminant function, the model of end-stage liver disease, the Glasgow Alcoholic Hepatitis score, and the ABIC score. While the former scores identify patients at risk of death or the need for corticosteroids, the response to corticosteroid therapy can be assessed using the Lille model. Treatments include abstinence and enteral nutrition, while pharmacotherapy using corticosteroids either with or without N-acetylcysteine may be indicated for patients with severe AH. Pentoxifylline was found to reduce the risk of hepatorenal syndrome, but data on mortality are limited. Although considered a contraindication in most transplant centers, recent evidence indicates that carefully selected patients with AH could be good candidates for liver transplantation with a prognosis comparable to other indications.- Abbreviations: ABIC - Acronym for Age, Bilirubin, INR, Creatinine; AH - Alcoholic hepatitis; ALD - Alcoholic liver disease; CYP2E1 - Cytochrome P450 2E1; DF - Discriminant function; GAHS - Glasgow alcoholic hepatitis score; HRS - Hepatorenal syndrome; KC - Kupffer cells; LPS - Lipopolysaccharides; MELD - Model for endstage liver disease; NAC - N-acetylcysteine; ROS - Reactive oxygen species; SIRS - Systemic inflamatory response syndrome; TEN - Total enteral nutrition; TNFα - Tumor necrosis factor alpha.